Modeling and characterization of the biochar electrodes for vanadium redox flow battery. (20th December 2021) - Yao, Sen; Zhou, Jiali; Zhang, Yajun; Hu, Jianjun; Xie, Tao
Abstract: A three-dimensional transient model of a vanadium redox flow battery (VRFB) with biochar electrode was developed in this study. The model was built to simulate the microscopic particle accumulation that is applicable to the biochar electrode. The electrode assembly was constructed using the classical mass transfer theory of porous media. The charge/discharge curves, cell efficiency, local current density distribution and species concentration distribution at various moments of time were investigated using this model. The results showed that the particle accumulation model of biochar electrode is both a realistic and reasonable approximation of events in the electrode. Analysis of the charg/discharg process and electrochemical reaction rates in the cell found that when the average particle radius of 1 × 10 −6  m, an electrode porosity of 0.3, an electrode thickness of 0.003 m and the average current density of 40 A/m 2, the charging voltage of the battery was lower and the discharging voltage was higher.